Utilization of the internet for physical activity and diet information and its influence on pregnant women's lifestyle habits in Qatar - Ayman Al-Dahshan; Vahe Kehyayan; Noora Al-Kubaisi; Nagah Selim (Frontiers Media S.A., 2023)
BackgroundMaintaining a healthy lifestyle during pregnancy is essential. With the increasing availability of the internet, pregnant women have access to a wealth of information related to physical activity (PA) and healthy diets.ObjectivesThe study aims to investigate the extent of internet usage by pregnant women attending antenatal clinics in Qatar to obtain information about PA and healthy diets, identify associated factors, and evaluate the impact of this information on their lifestyle habits.MethodsA cross-sectional study was conducted in six randomly selected public antenatal clinics in Qatar. Pregnant women aged ≥18 years in any trimester were recruited using a probability sampling technique. Data were collected through self-administered questionnaires. Descriptive and analytic statistics were employed for data analysis.ResultsA total of 327 pregnant women (mean age of 29.5 years ± 4.0) completed and returned the questionnaire (response rate: 87.5%). Among the participants, 54.5% used the internet to obtain information about PA, while 72% sought online diet-related information. Factors such as age (26-35 years), tertiary education, employment status, and being primigravidae were associated with a higher likelihood of using the internet for healthy lifestyles information. Participants who reported using the internet for PA information a great deal were more likely to increase their PA during pregnancy compared to those who used it somewhat or very little (57.6, 26.8, and 5.0%, p < 0.001; respectively). Similarly, those who used the internet for diet information a great deal were more likely to increase their fruit and vegetable consumption compared to those who used it somewhat, or very little (84.2, 68.5, and 63.6%, p = 0.038; respectively). Also, participants who used the internet for diet information a great deal were more likely to decrease the amount of sugary and fatty foods they ate compared to women who used the internet somewhat or very little (61.4, 45.2, and 18.2%, p < 0.001; respectively) and (50.9, 30.4, and 18.2%, p = 0.001; respectively).ConclusionMany pregnant women use the internet to access information about PA and diet, and greater use is associated with more positive lifestyle changes. This study provides useful information to consider when designing intervention programs for pregnant women about adopting and maintaining healthy lifestyles.